Constraints of cold and shade on the phenology of spring ephemeral herb species. (14th September 2016) - Augspurger, Carol K.; Salk, Carl F.
Summary: Spring ephemeral herb species in temperate deciduous forests are active above‐ground only briefly each year. This study tested experimentally how two countervailing constraints – cold and darkness – influence the phenology of six spring herb species. Dormancy of underground structures, maintained by cold temperatures in a growth chamber, was broken at six 25‐day intervals from January or February to June in two consecutive years. Upon emergence, survival and flowering were measured on cohorts grown outdoors. Shade cloth was added at the time of normal canopy closure. Cardamine concatenata, Dicentra cucullaria, Erythronium albidum and Trillium recurvatum had no or low 2‐year survival in the two or three earliest cohorts and no or low survival in the latest cohort, relative to their natural cohort. Allium canadense and Claytonia virginica had survival in all cohorts. Flowering never occurred in the first two or three cohorts for three species and never occurred or declined in later cohorts in all species. Despite widely differing emergence dates, senescence was completed within a 40‐day period soon after shade was imposed for all cohorts for all species. Consequently, leaf life span became shorter as date of emergence was delayed among cohorts. In general, the brief growth period of spring herb species is an adaptation to avoid winter cold and late‐spring canopy shade. These constraints are species‐specific and differ for survival and flowering for some species. Claytonia virginica is the most tolerant among the species to a wider range of conditions. Synthesis . Knowing that cold and shade constrain a plant's non‐dormant period is important because of the significant role plant phenology plays in responses to climate change. Abstract : This experiment that altered the natural phenology of spring ephemeral herb species in temperate deciduous forest demonstrates that cold temperatures in early spring and canopy shade in late spring lower the survival and reproduction of most species. These constraints explain their ephemeral phenology. The results indicate their potential vulnerability to shifting patterns of frost and shade with climate change.